Peranan Tarbiyah Halakah Pada Wahdah Islamiyah, Lembaga Dakwah Kampus Al-Insyirah, Dan Forum Komunikasi Mahasiswa Islam Al-Balagh Dalam Membentuk Akhlak Pemuda Muslim Di Watampone - Darwis, Darwis (JURNAL AL-QAYYIMAH, 2019)
This thesis presents the research about the important Tarbiyah Halakah at Wahda Islamiyah, LDK Al-Insyirah, and FKMI Al-Balagh form the morals of muslim. The subject matter is how form contribution of Tarbiyah Halakah Wahdah in Watampone. The research aim to know how the implementation form of tarbiyah halakah at wahdah islamiyah, LDK Al-Insyirah, dan FKMI Al-Balagh in form of morals the youth men in watampone. This research useful as the contribution of thought in maximizing the potential of muslim youth. This problems is presented by using Teologic Normatif approach, paedagogic and sosiologic and presented by using qualitative and by descriptive qualitative. Based on the result of the research it can be seen that form of implementation Tarbiyah halakah through several stages the beginning of recruitment then continued with division of groups tobe given intensive coaching Wahdah Islamiyah, LDK Al-Insyirah and FKMI Al-Balagh has a great contribution to cultivate and establish moral of youth muslim in Watampone. It can be seen of the youth who have joined in tarbiyah halakah to show the things are very positive to show the noble character to Allah Swt. Nor to the people who are inhis around.